A magnetic snapshot survey of F-type stars. Issue 4 (24th April 2020) - Seach, J M; Marsden, S C; Carter, B D; Neiner, C; Folsom, C P; Mengel, M W; Oksala, M E; Buysschaert, B
ABSTRACT: We present a spectropolarimetric magnetic snapshot survey of 55 stars which includes 53 F-type stars ranging from spectral types F0 to F9 plus 2 chemically peculiar stars β CrB, and δ Cap. We look for magnetic fields in stars spanning a range of effective temperatures where the transition from fossil to dynamo magnetic fields is believed to occur. High-resolution spectropolarimetry using circularly polarized spectra is used to look for a magnetic detection in the Stokes V profile, determine the mean longitudinal magnetic field ( Bl ), and to look for correlations with stellar parameters. Surface magnetic fields are detected on 14 F-stars, and present in every spectral class from F3V-F9V ranging in strength from 0.3 ± 0.1 G (36 UMa, F8V) to 8.3 ± 0.9 G (h Dra, F8V). Thus we find photospheric magnetic fields are present in stars as early as spectral type F3V with an outer convection zone thickness less than a few per cent of the stellar radius.